Consumer’s Dilemma: Vulnerability of Banks in India Versus Crypto Currency Adaptability - Bhattacharjee, Sandeep (Indian Journal of Computer Science, 2018)
Today’s banking system has seen revolutionary change within a decode or more. The foremost reason being the adaptation of information technology in the banking system. Although , this has strengthened the economy of our country, it has also led to many frauds and scams in the recent times. In this research paper, we have tried to collect information on the above events and tried to preview the actual positioning of India’s banking system. There has also been someÂ discussion on the understanding, growth, usability and adaptability of crypto currencies such as Bitcoins, Ethereum, Litecoin, Dash etc. The overall discussion helps us to understand how the inner complexities of Indian banking system is leading to consumer’s thoughts and interest shifting towards crypto currency. Some suggestions have also been provided as different steps which can be taken in the present situation.